2022
DOI: 10.4240/wjgs.v14.i5.429
|View full text |Cite
|
Sign up to set email alerts
|

Para-aortic lymph node involvement should not be a contraindication to resection of pancreatic ductal adenocarcinoma

Abstract: BACKGROUND Para-aortic lymph nodes (PALN) are found in the aortocaval groove and they are staged as metastatic disease if involved by pancreatic ductal adenocarcinoma (PDAC). The data in the literature is conflicting with some studies having associated PALN involvement with poor prognosis, while others not sharing the same results. PALN resection is not included in the standard lymphadenectomy during pancreatic resections as per the International Study Group for Pancreatic Surgery and there is no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…As PALN + status is captured in the N-status, with 79% of PALN + patients having N2 disease, the value of the N-classification may thus be superior to PALN + status when assessing overall survival. These findings are in line with other studies [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…As PALN + status is captured in the N-status, with 79% of PALN + patients having N2 disease, the value of the N-classification may thus be superior to PALN + status when assessing overall survival. These findings are in line with other studies [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…In this context, considering metastatic PALN as a contraindication to pancreaticoduodenectomy (PDD) in up-front resectable pancreatic cancer is a source of fiery debate [9][10][11] . Some studies have shown that patients with metastatic PALN could still benefit from radical PDD compared to the double bypass procedure 7 and benefit from modern chemotherapy regimens 3,6 .…”
Section: Resultsmentioning
confidence: 99%
“…However, there is no consensus on the dissection of a 16b1 group 16 . Recent studies showed that PALN involvement might not affect survival in patients who complete the full curative strategy (adequate systemic treatment and radical surgery) 6 , 8 , 15 . Thus, we systematically perform PALN dissection with frozen-section analysis in order to guide a personalized surgical approach, as follows:…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mOS of patients with advanced PC with a history of surgery was much greater than that of patients without a history of surgery (44.2 months vs. 10 months), a result that is consistent with widespread public perception. The study of surgery and survival of PC patients in a broad sense dates back to the 1970s and 1980s [26,27] ; then interest in factors affecting postoperative survival began and numerous studies were done, when lymph node metastasis was considered the most important postoperative prognostic factor [28,29] ; with progressive research, the prognosis of surgical treatment of PC is more carefully studied today, for example para-aortic lymph nodes are not a contraindication to PC surgery [30] ,…”
Section: Discussionmentioning
confidence: 99%